2013
DOI: 10.1186/1471-2458-13-1096
|View full text |Cite
|
Sign up to set email alerts
|

Children, parents and pets exercising together (CPET): exploratory randomised controlled trial

Abstract: BackgroundLevels of physical activity (PA) in UK children are much lower than recommended and novel approaches to its promotion are needed. The Children, Parents and Pets Exercising Together (CPET) study is the first exploratory randomised controlled trial (RCT) to develop and evaluate an intervention aimed at dog-based PA promotion in families. CPET aimed to assess the feasibility, acceptability and potential efficacy of a theory-driven, family-based, dog walking intervention for 9–11 year olds.MethodsTwenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 54 publications
1
63
0
Order By: Relevance
“…Three studies employed an intervention specifically to reduce SB,40 44 63 16 studies aimed at increasing PA levels,30 35 36 39 41 46 48 49 55 58–60 64 66 72 78 nine studies combined both approaches of reducing SB and increasing PA levels,32 43 53 62 65 68 70 76 77 one study assessed the effect of a dietary intervention on SB,61 and 22 studies (20 reports) applied a multicomponent lifestyle intervention and observed effects on sedentary behaviour (among other outcomes) 29 33 34 37 38 42 45 47 50–52 54 56 57 67 69 71 73 74 75. Twenty studies offered an alternative intervention,30 36 39–41 45 46 49 52–55 59 61–63 68 72 77 10 studies the usual/routine care,29 37 38 42 50 51 67 71 74 75 seven studies used a waiting list control,29 34 48 64 69 76 78 five studies an attention control,35 44 56 57 60 and control participants of seven studies received no intervention at all 32 33 43 47 58 66 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies employed an intervention specifically to reduce SB,40 44 63 16 studies aimed at increasing PA levels,30 35 36 39 41 46 48 49 55 58–60 64 66 72 78 nine studies combined both approaches of reducing SB and increasing PA levels,32 43 53 62 65 68 70 76 77 one study assessed the effect of a dietary intervention on SB,61 and 22 studies (20 reports) applied a multicomponent lifestyle intervention and observed effects on sedentary behaviour (among other outcomes) 29 33 34 37 38 42 45 47 50–52 54 56 57 67 69 71 73 74 75. Twenty studies offered an alternative intervention,30 36 39–41 45 46 49 52–55 59 61–63 68 72 77 10 studies the usual/routine care,29 37 38 42 50 51 67 71 74 75 seven studies used a waiting list control,29 34 48 64 69 76 78 five studies an attention control,35 44 56 57 60 and control participants of seven studies received no intervention at all 32 33 43 47 58 66 …”
Section: Resultsmentioning
confidence: 99%
“…Control conditions were attention control60 and an alternative exercise treatment 39. Twenty-four studies suggested no evidence of a group difference in SB: 10 lifestyle interventions,29 45 50 52 56 57 67 71 73 75 seven PA interventions,35 36 49 55 58 66 72 six PA/SB interventions,53 62 65 70 76 77 and one SB intervention 44. Four studies—two lifestyle,47 69 one PA/SBs,43 one dietary intervention61—did not conclude on SB outcomes despite assessing SB.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the current study, six dog walking intervention studies have been published to date (Byers et al, 2014;Johnson & Meadows, 2010;Kushner, Blatner, Jewell, & Rudloff, 2006;Morrison et al, 2013;Rhodes, Murray, Temple, Tuokko, & Higgins, 2012;Schneider et al, 2015). Four of these interventions were randomized controlled trials (RCT; Byers et al, 2014;Morrison et al, 2013;Rhodes et al, 2012;Schneider et al, 2015), and only one was based on a health behavior theory, specifically, social cognitive theory (SCT; Morrison et al, 2013).…”
Section: Pa and Dog Walkingmentioning
confidence: 98%
“…Four of these interventions were randomized controlled trials (RCT; Byers et al, 2014;Morrison et al, 2013;Rhodes et al, 2012;Schneider et al, 2015), and only one was based on a health behavior theory, specifically, social cognitive theory (SCT; Morrison et al, 2013). Only three of the interventions had any type of follow-up postintervention, and this follow-up was limited to 3 months or less (Byers et al, 2014;Morrison et al, 2013;Rhodes et al, 2012).…”
Section: Pa and Dog Walkingmentioning
confidence: 99%
“…Furthermore, a randomized controlled trial involving an intervention program encouraging parents to go dog walking along with their children (Children, Parents, and Pets Exercising Together: CPET) 34) was conducted in the United Kingdom (UK). The main objective was to increase the physical activity level of children.…”
Section: Interventions For Promoting Dog Owner Physical Activitymentioning
confidence: 99%